PENERAPAN INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KOLABORASI SISWA PADA PEMBELAJARAN IPAS SD - Afiyah, Anggi Nur; Zulkarnaen, Zulkarnaen (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Science learning at SDN 04 Nagur still faces various challenges, including the dominance of the teacher's role, low active student participation, and minimal integration of local values ??in the learning process. The impact is seen in the low development of students' skills in critical thinking and effective collaboration. As an effort to overcome these problems, a guided inquiry learning model is applied which is designed to develop 21st century skills through stages of scientific thinking and group cooperation. The purpose of this study is to analyze the effectiveness of the application of the guided inquiry learning model in improving critical thinking and collaboration skills of students in class VI B SDN 04 Nagur. This study relies on a qualitative approach with data collection techniques in the form of observation, interviews, and documentation to explore the application of the guided inquiry model that is adjusted to student characteristics, such as interests, learning styles, levels of understanding and age of students at the concrete operational stage. Based on the results of the study, it is known that the guided inquiry model has proven effective in increasing student involvement during learning, developing their abilities in formulating problems, compiling data-based solutions, and instilling awareness of local cultural values. However, some obstacles faced such as low student confidence during presentations, and lack of initial understanding of local culture. The solutions implemented include the use of scaffolding, peer tutoring, think-pair-share strategies, and the integration of local values ??into learning materials. The conclusion of this study shows that the implementation of the guided inquiry learning model is effective in improving students' critical thinking and collaboration skills, and is relevant to be applied in contextual science learning based on local characters. ABSTRAKPembelajaran IPAS di SDN 04 Nagur masih menghadapi berbagai tantangan, antara lain dominasi peran guru, rendahnya partisipasi aktif siswa, dan minimnya integrasi nilai-nilai lokal dalam proses pembelajaran. Dampaknya terlihat pada rendahnya perkembangan keterampilan siswa dalam berpikir kritis serta kolaboratif secara efektif. Sebagai upaya untuk mengatasi permasalahan tersebut, diterapkan model pembelajaran inkuiri terbimbing yang dirancang untuk mengembangkan keterampilan abad ke-21 melalui tahapan berpikir ilmiah dan kerja sama kelompok. Tujuan dari penelitian ini adalah menganalisis efektivitas penerapan model pembelajaran inkuiri terbimbing dalam meningkatkan keterampilan berpikir kritis dan kolaborasi siswa di kelas VI B SDN 04 Nagur. Penelitian ini mengandalkan pendekatan kualitatif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi untuk mengeksplorasi penerapan model inkuiri terbimbing yang disesuaikan dengan karakteristik siswa, seperti minat, gaya belajar, tingkat pemahaman serta usia siswa pada tahap operasional konkret. Berdasarkan hasil penelitian, diketahui bahwa model inkuiri terbimbing terbukti efektif dalam meningkatkan keterlibatan siswa selama pembelajaran, mengembangkan kemampuan mereka dalam merumuskan masalah, menyusun solusi berbasis data, serta menanamkan kesadaran akan nilai budaya lokal. Meski demikian, beberapa hambatan yang dihadapi seperti rendahnya rasa percaya diri siswa saat presentasi, serta kurangnya pemahaman awal terhadap budaya lokal. Solusi yang diterapkan antara lain penggunaan scaffolding, peer tutoring, strategi think-pair-share, serta integrasi nilai-nilai lokal ke dalam materi pembelajaran. Simpulan dari penelitian ini menunjukkan bahwa penerapan model pembelajaran inkuiri terbimbing efektif dalam meningkatkan keterampilan berpikir kritis dan kolaborasi siswa, serta relevan untuk diterapkan dalam pembelajaran IPAS kontekstual berbasis karakter lokal.